A river called beautiful - Chor, Jee Chow, 1929- (Singapore : Landmark Books, 1997)
Autobiography of Chor Jee Chow, b. 1929, a Chinese American.
Keywords: Chor, Jee chow, -- 1929-; Singapore -- Biography